Analysis Of Innovative Learning Media For Teaching Fractions: A Case Study On Pre-Service Mathematics Teachers’ Creativity - Nursanti, Yuli Bangun; Nurhasanah, Farida (International Journal on Emerging Mathematics Education, 2024)
The ability to think creatively is not only an individual's ability to analyze based on existing information but also collectively be able to produce new and determine alternatives with various ideas. It needs to be developed among pre-service teachers so they can use it to design their lessons. This study aims to analyze the creativity of pre-service mathematics teachers in designing and developing innovative learning media for teaching fractions. The research used a qualitative approach with a descriptive method and was conducted in class with 42 students. The data was collected from their product of learning media and filling questionnaires through Google Classroom. From the result, we can conclude that the development of student's creative thinking abilities through the creation of innovative learning media is involved in the modification of the creative model, where they make the product more attractive and practical through content and how to present the media.